Écrits - Berg, Alban 1885-1935; Pousseur, Henri 1929-2009 (Monaco-Ville Rocher, 1957)
Alban Berg's “fortune” was a strange one: loved and honored during his lifetime, occupying his historic place in the Viennese School, it wasn't until his final years in France that the feeling that he was one of the main architects of our modernity was shared without reservation. The composer wrote. Texts of a very diverse nature: aesthetic, polemical, historical, analytical. Some were known to French music lovers, but had become impossible to find. The present publication is the first general edition of the Ecrits, with many previously unpublished works in French. There is no doubt that this collection will lead to a better understanding of the composer of Wozzeck and Lulu, now indispensable to our musical and human culture. (Translated with DeepL.com)
Keywords: Composer; Correspondence; Music philosophy and esthetics; Music criticism; Musical analysis